Effects of cold water immersion after exercise on fatigue recovery and exercise performance–meta analysis - Xiao, Feiyan; Kabachkova, Anastasiia V.; Jiao, Lu; Zhao, Huan; Kapilevich, Leonid V. (Frontiers in Physiology, 2023)
This systematic review aims to examine the effect of cold water immersion (CWI) on fatigue recovery after high-intensity exercise and exercise performance. A total of 20 studies were included in this review. Analyses of subjective indicators such as delayed-onset muscle soreness (DOMS) and ratings of perceived exertion (RPE), and objective indicators such as countermovement jump (CMJ) and blood plasma markers including creatine kinase(CK), lactate/lactate dehydrogenase(LDH), C-reactive protein(CRP), and IL-6 were performed. Pooled data showed as follows: CWI resulted in a significant decline in subjective characteristics (delayed-onset muscle soreness and perceived exertion at 0 h); CWI reduced countermovement jump(CMJ) significantly at 0 h, creatine kinase(CK) was lowered at 24 h, and lactate at 24 and 48 h. There was no evidence that CWI affects C-reactive protein(CRP) and IL-6 during a 48-h recovery period. Subgroup analysis revealed that different CWI sites and water temperatures have no effect on post-exercise fatigue recovery.